Ohranjanje regionalne raznolikosti stanovanjske hiše v Sloveniji - Drozg, Vladimir (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
The article deals with the problem of preserving a regional variety of new constructions and the way how to incorporate the preserving regime in the system of settlement regulation. Two questions were discoused: 1. what to preserve - which morphological features of authentic construction should new constructions imitate in order to preserve the regional identity of the buildings? and 2. how to preserve - how should regulations be incorporated into the system of settlement regulation?
Keywords: fiziognomija; hiše; naselja; podeželje; rural area; Slovenia; Slovenija; stanovanjske zgradbe; urejanje prostora